PENDIDIKAN KEAKSARAAN UNTUK MENCERDASKAN KEHIDUPAN MASYARAKAT - Sodiq A. Kuntoro (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Literacy/illiteracy is not a simple matter. It does not only show whether a person can read and write words and letters, but also whether a person can face complicated problems of human life. Illiterate persons usually have weaknesses in understanding their own problems comprehensively. They suffer from an inferiority state of mind. They usually feel less important than others as they are unable to solve their own problems. Literacy education for youths and adults as a movement to improve the human life condition, therefore, should not be understood in a technical level i.e. teaching reading and writing letters and words. Words are not empty. Words represent human thought about world and reality. They also represent the users’ desire to do something. So, literacy education for youths and adults must be designed to improve the learners’ cognition, and to develop a new perspective of self-consciousness in relation to the willingness to cope with the learners’ life problems. The youths and adults learning activities must be based on transformative perspective, as they have been involved in the social development. The learning activities must transform them to be active participants or agents in the social development. Literacy education indeed must be considered in a wider understanding and not in a simple one.